Konsep Teologi Dispensasional - Remita Nian Permata Zendrato; Miraniat Hati Gulo; Tupa Sihombing; Adi Suhenra Sigiro (Sukacita : Jurnal Pendidikan Iman Kristen, 2025)
Dispensational theology is a system of biblical interpretation that views the history of salvation as a series of periods or dispensations in which God interacts with humanity in different ways, each with distinct rules and responsibilities. This writing aims to understand the development of the concept of dispensationalism, its literal method of interpretation, and the differing perspectives between Israel and the Church in God's plan. The method used is a literature review, analyzing various scholarly works and theological sources. The study's findings indicate that dispensationalism emphasizes a literal interpretation of the Bible, makes a clear distinction between Israel and the Church, and understands God’s promises as being fulfilled literally in the future. This system continues to develop and remains relevant in contemporary Christian theological discourse, including in Indonesia.